Molecular basis for D− Japanese: identification of novel DEL and D− alleles. Issue 4 (7th May 2015) - Ogasawara, K.; Suzuki, Y.; Sasaki, K.; Osabe, T.; Isa, K.; Tsuneyama, H.; Uchikawa, M.; Satake, M.; Tadokoro, K.
<x xml:space="preserve">Abstract</x> Background and Objectives The occurrence of D− is approximately 0·5% in Japanese, but DEL in apparently D− individuals is relatively common compared with that in Caucasian populations. On the basis of molecular genetics, we examined D− Japanese blood donors. Methods A standard serological technique was used for RhD typing, and we selected 3526 D− blood samples. Genomic DNA obtained from whole blood was used for RHD analysis by polymerase chain reaction (PCR) and sequencing. Multiplex PCR to detect all of the RHD exons and use of PCR‐sequence‐specific primer (PCR‐SSP) to detect RHD deletion (RHD*01N.01) and c.1227G>A mutation (for RHD*01EL.01) were performed. Results Multiplex PCR and PCR‐SSP revealed that 3091 of 3526 D− individuals (87·7%) were homozygous for RHD*01N.01, and 318 individuals (9·0%) had the RHD*01EL.01/RHD*01N.01 or RHD*01EL.01/RHD*01EL.01 genotype. The other 103 in the 3526 individuals (2·9%) had the known D‐CE‐D hybrid allele, RHD*01N.04, and the association of RHCE*Ce with RHD*01EL.01 as well as RHD*01N.04 was observed. The remaining 14 individuals had RHD*01N.01 hemizygous with one of the following alleles: RHD*01N.06 (3), RHD*01N.07 (1), RHD*04N.01 (1), RHD*DEL8 (1), RHD with c.761C>G (p.Ser254Ter) (2), RHD with c.1252T>A (p.Ter418Lysex26) (2) and apparently common RHD (4). Adsorption and elution tests with anti‐D revealed that the individuals with c.761C>G mutation were D− while the individuals with c.1252T>A mutation were DEL. Conclusions The RHD genotype of more than 96% of D− Japanese could be determined by conventional PCR‐SSP. In addition, we identified a novel DEL allele having c.1252T>A mutation and a novel RHD silencing allele having c.761C>G nonsense mutation.